+0  
 
0
2
37
5
avatar

1.) 3x-2x^2=7

2.)5-2x^2=6x

3.)(x+3)(x+4)=0

4.)(2x+7)(x+4)=0

5.)2x(x-3)=15

plss help

 
Guest Jun 18, 2017
social bar
Sort: 

5+0 Answers

 #1
avatar+74552 
+1

 

We want the form  ax^2 + bx + c = 0

 

1. 3x - 2x^2  = 7   re-write as

-2x^2 + 3x - 7  = 0

a = -2, b = 3, c = -7

 

2.  5 - 2x^2  = 6x    re-write as

-2x^2 - 6x + 5 = 0

a = -2, b = -6, c = 5

 

3. (x + 3) ( x + 4)  = 0   expand as

x^2 + 3x + 4x + 12 = 0

x^2   +  7x + 12  = 0

a =1. b = 7, c  = 12

 

4. (2x + 7) ( x+ 4)  = 0  expand as

2x^2 + 7x + 8x + 28   =  0

2x^2  + 15x + 28  = 0

a = 2, b = 15, c = 28

 

5.  2x ( x - 3)   = 15

2x^2 - 6x  = 15

2x^2 - 6x - 15 = 0

a = 2, b = -6, -15

 

 

 

cool cool cool

 
CPhill  Jun 18, 2017
 #4
avatar
0

lastly 

(2x-1)^2=3(x+1)2

 
Guest Jun 18, 2017
 #2
avatar
0

and there's more 

1.)(x+7)(x-7)=-3x

2.)(x-4)^2+8=0

3.)(x+2)^2=3(x+2)

4.)(2x-1)^2=(x+1)^2

5.)2x(x+4)=(x-3)(x-3)

thank you cphill god bless you

 
Guest Jun 18, 2017
 #3
avatar+74552 
+1

 

1. (x + 7) ( x - 7)  = -3x

x^2 - 49 = -3x

x^2 + 3x - 49 = 0

a = 1, b = 3, c = -49

 

2. (x - 4)^2 + 8 = 0

(x - 4) ( x- 4) + 8 =0

x^2 - 4x - 4x + 16 + 8 =0

x^2 - 8x + 24 = 0

a = 1, b = -8, c = 24

 

3.  ( x + 2 )^2  = 3 ( x + 2)

(x + 2)^2 - 3 (x + 2 ) = 0

(x + 2) ( x + 2) - 3(x + 2)  = 0

x^2 + 2x + 2x + 4 - 3x - 6  = 0

x^2 + 4x + 4 - 3x - 6  = 0

x^2 + x - 2  = 0

a = 1, b = 1, c = -2

 

4. (2x + 7) ( x + 4)   = 0

2x^2 + 7x + 8x + 28  = 0

2x^2 + 15x + 28  = 0

a = 2 , b =  15, c = 28

 

5. 2x( x + 4)  =  (x -3) ( x - 3)

2x^2 + 8x  - (x - 3) ( x - 3)  = 0

2x^2 + 8x -  [ x^2 - 6x + 9 ]  = 0

2x^2 + 8x - x^2 + 6x - 9  = 0

x^2 + 14x - 9  = 0

a = 1, b = 14, c = -9

 

 

cool cool cool

 
CPhill  Jun 18, 2017
edited by CPhill  Jun 18, 2017
edited by CPhill  Jun 18, 2017
 #5
avatar+74552 
+1

 

(2x - 1)^2 = 3(x + 1)^2

 

(2x - 1) ( 2x - 1)  =  3( x + 1) ( x + 1)

 

4x^2 - 2x - 2x + 1  =  3 ( x^2 + 1x + 1x + 1)

  

4x^2 - 4x + 1  =  3 ( x^2 + 2x + 1)

 

4x^2 - 4x + 1  =  3x^2 + 6x + 3   simplify

 

x^2 - 10x - 2  =  0

 

a = 1,  b = -10,  c = -2

 

 

cool cool cool

 
CPhill  Jun 18, 2017

13 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details